Is There a Gap between Practitioners’ and Academicians’ Perceptions on Business Graduates’ Competencies in Malaysia? - Tzu, Shirley Ken (Journal of Education and Vocational Research, 2012)
There is always a gap between practitioners’ perception on business graduate competencies as compared to academicians’ perception on the similar topic. Hence, the task to bridge the gap is very necessary in order to equipped business graduates with a more competent set of skills. This study aims to empirically identify the practitioners’ perception on important competencies should possessed by Malaysia business graduates. The second objective is to identify the practitioners’ perception on important competencies should possessed by Malaysia business graduates. Last objective is to identify if there is a gap exist between both group’s perception on important competencies should possessed by Malaysia business graduates. A survey questionnaire was designed and administered to determine the perceptions of employers about the perceived important competencies and hiring preferences. A total of 45 questionnaires were distributed to managers of nine main local commercial banks in Malaysia in the period of six months. The gap between employer needs and graduate competencies were able identified. The findings from this study can be a significant help to the universities in producing competitive business graduates and industries at improving human capital capabilities.